PERAN ICT DALAM MODERNISASI PENDIDIKAN PONDOK PESANTREN - Sholihah, Ummu (IAIN Ponorogo, 2012)
Abstract: The advancement of Information and Communications Technology has led to the modernization of education especially in Islamic boarding school. Modernization of education in Islamic boarding school is one of ways to counter the negative assumption of the society who think that it is just as traditional educational institution. Modernization of education is not only aimed at creating excellent Islamic aspiring cadres, but also purposed to create great scholars who can nurture and develop the nation and society. One of modernization forms is by using information communication technology (ICT) in educational process. The use of ICT has raised the concept of e-Islamic boarding school. It provides a lot of benefits for the students, teachers, and school principle to increase the quality of process and outcome of learning, teaching practice, and management of educational program. Beside that, the integration of ICT in the educational system has improved the quality of education and eased to get the propagation purposes. The positive wash back of the integration of ICT in educational process is that it encourages the acceleration of computer literacy on our society.